Growth/Life form analysis of the lichenobiota in the Yelanetsko- Ingulskiy region (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Analysis of life forms is done for the lichen-forming fungi in the Yelanetsko-Ingulskiy region. We recognize 19 growth forms of lichen thalli here.
Keywords: endocarpic life form, epithalline life form, lichenized fungi, life form, thallus.